2016
DOI: 10.1007/s13346-016-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the hydrodynamic conditions of the eye to better reproduce the drug release from hydrogel contact lenses: experiments and modeling

Abstract: Currently, most in vitro drug release studies for ophthalmic applications are carried out in static sink conditions. Although this procedure is simple and useful to make comparative studies, it does not describe adequately the drug release kinetics in the eye, considering the small tear volume and flow rates found in vivo.In this work a microfluidic cell was designed and used to mimic the continuous, In conclusion, the use of the microfluidic cell in conjunction with the numerical model shall be a valuable too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…An increased drug release in the presence of PEGDA hydrogel in the dynamic condition is likely due to the polymer/drug layer in contact with a larger amount of water content in the hydrogel. This is consistent with a finding by Pimenta et al, who compared diclofenac release from hydroxyethyl methacrylate-based hydrogel [49], where 90% diclofenac release was attained by 100 hours in dynamic flow, as compared to 24 hours in static condition.…”
Section: Discussionsupporting
confidence: 92%
“…An increased drug release in the presence of PEGDA hydrogel in the dynamic condition is likely due to the polymer/drug layer in contact with a larger amount of water content in the hydrogel. This is consistent with a finding by Pimenta et al, who compared diclofenac release from hydroxyethyl methacrylate-based hydrogel [49], where 90% diclofenac release was attained by 100 hours in dynamic flow, as compared to 24 hours in static condition.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, because most used ophthalmology in vitro drug release study is carried out under static conditions, and are not fully considering the influence of flow dynamics, need to take into account the tear volume and flow in the body, Pimenta et al [ 104 ] designed a microfluidic unit to simulate the tear continuous, the volumetric flow rate, and its small volume. The release kinetics of a drug system containing diclofenac was compared with that under static condition by using the microfluidic chip, and the results showed that the release kinetics under dynamic condition was slower.…”
Section: In Vitro Biomechanical Study Methods Of Eye Tissuementioning
confidence: 99%
“…Since the lack of hydration results in dry eye syndrome [148], it is recommended to use contact lenses in association with eye drops [149].…”
Section: Contact Lensesmentioning
confidence: 99%